"Can We Vaccinate Everybody?" A Rehabilitation Ward's Experience of an Inpatient COVID-19 Vaccination Program. (March 2022) - Dalton, Catherine; Lafeuillee, Gisele
Gwynne Holford Ward (GHW) is an inpatient rehabilitation Unit at Queen Mary's Hospital in London, UK, which provides care for patients with amputation rehabilitation needs (10 beds) as well as Level 1 and 2 specialist neurorehabilitation needs (26 beds). The ward MDT has encouraged all inpatients to be vaccinated either during or prior to admission. We have conducted a weekly snapshot audit over a 3-week period in March 2021, which has shown an increase of the percentage of inpatients vaccinated, progressively from 68.75% to 80%, and 73% of vaccinated inpatients received the vaccine whilst on the ward. We also conducted inpatient interviews, which highlighted that: (1) opening dialogue about vaccines increased uptake of COVID-19 vaccine; (2) patients felt that all vaccination sites provided quick, efficient service; and (3) all patients who received the first COVID-19 vaccine were willing to have the second COVID-19 vaccine. Finally, although there were many hurdles faced whilst organizing the inpatient vaccination process, we have been able to cumulatively vaccinate 80% of rehabilitation inpatients making our ward a safer place to work and rehabilitate.